Submandibular gland excision - Carvalho,Alexandre Sanfurgo de (2015)
OBJECTIVE: to analyze the value of fine needle aspiration and the rates of postoperative complications in patients undergoing resection of the submandibular gland. METHODS: we analyzed the records of patients treated with resection of the gland from January 1995 to December 2008. The data collected included age, gender, findings on clinical history, surgical procedure, results of fine needle aspiration (FNA), pathological diagnosis and complications. RESULTS: 117 patients were studied, aged 12-89 years (mean 48), 70 women and 47 men. Thirty-nine patients (33.3%) were affected by inflammatory diseases (28 patients with lithiasis), 70 had benign tumors, and malignant tumors, eight. Regarding FNA, the sensitivity and specificity were 85.7% and 100%, respectively. Nine patients (7.7%) had temporary paralysis of the marginal mandibular nerve and one had permanent paralysis. CONCLUSION: resection of the submandibular gland is a safe procedure, with low complication rates.